Thyrotoxicosis occurrence in SARS-CoV-2 infection: A case report - Pranasakti, Maria Erika (Elsevier Ltd, 2022)
Introduction: Coronavirus Disease 2019 (COVID-19) is predominantly manifested as respiratory distress. There are growing reports of extrapulmonary clinical manifestations of COVID-19 in addition to the respiratory symptoms. COVID-19 has been associated with the thyroid function through Angiotensin-converting enzyme 2 (ACE2), the central mechanism through Thyroid Stimulating Hormone (TSH), and direct replication of the virus. Case presentation: A 26-year-old woman presented with complaints of palpitation and abdominal pain for three days. Because the symptoms were worsening, she was brought to the emergency room. Her temperature was 37.9 °C without any symptoms of cough, coryza, sneezing, nor headache. Physical examination revealed tremor, tachycardia with 162 beats per minute (bpm), excessive sweating, hyperreflexia of patellar reflex, and no prominent lump in the neck. Electrocardiography (ECG) showed supraventricular tachycardic rhythm (SVT) and 150 J cardioversions were performed. The ECG converted to sinus rhythm, regular, with 120 bpm. Thyroid function tests showed an elevated fT4 level (>7.77 ng/dL) and low TSH level (<0.005 μIU/mL). Chest X-ray showed slight cardiomegaly without prominent abnormality in the lungs that was confirmed with thoracic computerized tomography. The result of the rapid antigen test for COVID-19 was positive and confirmed with polymerase chain reaction testing. She was then treated in the intensive isolation room with remdesivir, anti-hyperthyroid, and supportive therapy. As her condition improved, she was shifted to a non-intensive isolation room and was discharged from the hospital at day 7. Discussion: COVID-19 could present as a thyroid crisis as the initial clinical manifestation. Clinicians should be aware that presentation of thyroid dysfunction in a patient without previous endocrine disease could be due to COVID-19 infection. Early recognition, anti-hyperthyroid therapy, and following isolation procedures for COVID-19 are required in the emergency condition. © 2022